Radish (Raphanus sativus L.) Cultivar‐Specific Response to O3: Patterns of Biochemical and Plant Growth Characteristics. Issue 6 (10th May 2018) - Hassan, Ibrahim A.; Bell, Nigel B.; Ashmore, Mike R.; Cotrozzi, Lorenzo; Haiba, Nesreen S.; Basahi, Jalal M.; Summan, Ahmad; Almeelbi, Talal; Ismail, Iqbal M.
Abstract : The sensitivity of four radish ( Raphanus sativus L.) cultivars, Baladey "B, " Cherry Belle "CB, " Prinz Rotin "PR, " and Scarlet Globe "SG" to 80 nL L −1 ozone is assessed in fumigation chambers. O3 visible injury symptoms appears as brown spots to chlorotic areas, but the response is cultivar‐specific. O3 induces higher content of H2 O2 and lipid peroxidation (it is estimated as malondialdehyde (MDA) content), leading to drastic visible injury symptoms in B compared to the other cultivars. Root and shoot dry weights, Chlorophyll a, net photosynthetic rates, and chlorophyll fluorescence are reduced in B to a greater extent than the other cultivars. On the other hand, stomatal conductance increased in B and CB (+52 and +24%, respectively) due to O3 ‐exposure, while it was decreased by 35% in PR and SG. Exposure to O3 generates oxidative stress leading to stimulation of antioxidative defense systems. SG shows the highest induction of catalase (CAT), superoxide dismutase (SOD), and glutathione reductase (GR), while B had the lowest activities of these antioxidative enzymes, but had the highest H2 O2 and MDA content. The higher accumulation of H2 O2, poor induction of antioxidative enzymes, and increased stomatal conductance led to severe visible injury and drastic inhibition in photosynthetic rates and growth in B than other cultivars depicting its higher sensitivity toward O3 . Therefore, it can be used as a bioindicator for O3 pollution worldwide. Abstract : O3 reduced both root dry weight (hypocotyl "RDW") and shoot dry weight (SDW) with cultivar B. Cultivar "B" proved to be very sensitive to O3, therefore, it can be used as a bioindicator species for O3 .